HEGEMONI DALAM BERITA PEMILIHAN CALON PRESIDEN DI MEDIA CETAK INDONESIA - Dwi Aksa, Yudha Asmara; Sandra N.S, Christina (Fakultas Komunikasi, Sastra, dan Bahasa, 2016)
This study analyzes the news hegemony framing of the presidential election (Election) in 2014 in Daily Newspaper Suara Pembaruan, particularly in the main report rubric from May to July 2014. 2014 Presidential Election?s news is the most interesting news for the media and the public because it attracts the public?s interest. At the time of the election, almost all media present the news as headline including Suara Pembaruan. By using descriptive qualitative method with Zhongdan Pan and Gerald M. Kosicki?s framing analysis model, this research aims to find out how Suara Pembaruan framed 2014 presidential elections.  The result shows that the news framing of 2014 presidential elections conducted by Suara Pembaruan mainly focused on Joko Widodo, the number 2 presidential candidate than the number 1 candidate, Prabowo